Effects of Monetary Policy Shocks on Inequality: A Proxy-Svar Approach - N. Mertens, Arnaud (Université d'Ottawa | University of Ottawa, 2019)
Inequality has been increasing in the United States over the past three decades. While several avenues have been explored to explain this rise, the role of monetary policy has only recently been considered. Moreover, the overall effects of monetary policy shocks on inequality remain ambiguous both theoretically and empirically. Therefore, I propose a new study of the effects of conventional monetary policy shocks on income inequality in the United States. To do so, I use a structural vector autoregression (SVAR) model with external instruments. It consists of taking series of monetary policy shocks as proxies for structural shocks. First, I provide evidence that contractionary monetary policy shocks significantly increase inequality in the long run. Second, by breaking the income distribution down into different groups, I show that the higher an income group in the distribution is, the more favored it is by contractionary shocks. Third, I find that the increase in income of the top 1% is strikingly symmetric to the decrease of the bottom 10% after a contractionary monetary policy shock. These findings suggest that the Fed’s actions play a role in long-term inequality.